A General Protocol for the Synthesis of H-α-Hydroxyphosphinates - Dussart, Jade; Deschamp, Julia; Monteil, Maelle; Gager, Olivier; Migianu-Griffoni, Evelyne; Lecouvey, Marc (Synthesis, 2019)
A general synthetic procedure was developed for H-α-hydroxyphosphinates via Abramov reaction. The present work is a complementary study to those reported till now. This methodology has the advantage that it can be applied to various aliphatic and (hetero)aromatic substrates. The H-α-hydroxyphosphinates were easily purified and obtained in good to excellent yields in shorter times. A 31P NMR spectroscopy study has shown that only 2 equivalents of a silylating agent were required.
Keywords: α-hydroxyphosphinate; synthetic methods; phosphorus; phosphonylation; H-phosphinate